Analysis of The Use of Digital Learning Media Technology in Science Lesson Materials in Primary Schools Based on The Philosophy Perspective of Progressivism - Nisa, Sharfina Khairun; Putri, Enjelina Regina; Irega Gelly gera (Edutech Publishing Media, 2023)
This research aims to investigate the use of digital learning media technology in teaching science in elementary schools by considering the perspective of progressivism philosophy. In an era of technology that continues to develop, digital media art is an important key to supporting the application of technology. The use of digital teaching materials, especially in science learning in elementary schools, is an innovation. It is hoped that the rapid and rapid development and progress of Information Technology Systems will be able to bring changes and positive impacts in various aspects of life, especially in the advancement of the world of education. Therefore, the world of education must continue to make updates in line with current developments to avoid being left behind in technological developments. A progressivism approach is applied to evaluate the impact of using technology on active interaction and student involvement in the learning process. The results of the analysis show that the application of digital learning media technology can effectively improve student understanding, skill development and stimulate critical thinking at the basic education level.